THEORY AND PRACTICE OF RESTING ENERGY EXPENDITURES EVALUATION OF THE PATIENTS IN THE INTENSIVE CARE DEPARTMENTS - S. M. Efremov; V. O. Talaban; V. V. Artemieva; M. N. Deryagin; V. V. Lomivorotov (Вестник анестезиологии и реаниматологии)
Nutritive support is the equally important component of the intensive care and it is impossible without the adequate evaluation of resting energy expenditures (REE) of a specific patient. This article describes the most common evaluation techniques of REE, among which the technique of the indirect calorimetry is the most informative. The review included calculation equations for REE evaluations studied the most. The most sensitive equation which informativeness is confirmed by prospective studies is Penn State formula, and the Harris-Benedict equation is not suitable for the use in the intensive care department. It is worth highlighting that the use of equations is acceptable only when the indirect calorimetry technique is not available.